Insight out get ideas out of your head and into the world - Seelig, Tina Lynn (HarperOne, An Imprint of Harper Collins Publishers, 2015)
"What if there were a clear set of instructions to help you bring your best ideas to life? As with a recipe, you could take a compelling idea and with concrete steps, transform it into something extraordinary.As a professor at Stanford University, Tina Seelig has dedicated her career to teaching the practice of moving from imagination to implementation. In Insight Out, she welcomes you into her classroom and crisply defines the core concepts of imagination, creativity, innovation, and entrepreneurship, presenting an elegant and much-needed model she calls the 'Invention Cycle.' This new approach enables you to see obstacles as opportunities, inspire others to share your vision, and ultimately bring more ideas to fruition.Filled with surprising research, examples from her Stanford classroom, and stories from around the world--Silicon Valley to San Quentin State Prison, rural Pakistan to the North Pole--Insight Out offers essential and unexpected strategies that will help bring even the slightest flicker of an idea to life. Equally useful for students, educators, entrepreneurs, and would-be innovators in all fields, this is an essential road map for anyone who wants to get ideas out of their head and into the world"-- Provided by publisher